A meta-analysis of chemokines in vitiligo: Recruiting immune cells towards melanocytes - Speeckaert, Reinhart; Belpaire, Arno; Speeckaert, Marijn M.; van Geel, Nanja (Frontiers in Immunology, 2023)
Chemokine research offers insightful information on the pathogenesis of cutaneous immune disorders, such as vitiligo. Compared to cytokines, the higher detectable levels of chemokines display promising potential as future disease biomarkers. Nonetheless, some published study results are contradictory, which can be attributed to patient characteristics and methodological differences. In this study, a meta-analysis was performed to compare chemokine expression in blood and skin samples from vitiligo patients versus healthy controls. Furthermore, the relationship between chemokine expression and disease activity was evaluated. Chemokine levels were investigated in 15 articles in the circulation and in 9 articles in vitiligo skin. Overall, some clear trends were observed. CXCR3 signaling by CXCL10 and CXCL9 has been confirmed by several reports, although CXCL10 showed more robust findings in blood samples. In this meta-analysis, CCL5, CXCL8, CXCL12, and CXCL16 levels were also significantly elevated. This indicates a complex immune pathway activation in vitiligo that overall supports a Th1-dominant response. Chemokines linked to the Th2 and Th17 pathways were less prevalent. Despite these findings, study protocols that examine a broader range of chemokines are encouraged, because current research is mostly focused on a small number of chemokines that were differentially expressed in previous studies.